Causes and Solutions to Adolescent Aversion to Learning - Guo, Wei (International Journal of Social Sciences and Public Administration, 2024)
Adolescents are the builders of the nation’s future and the successors of the Chinese nation’s cause. Books are the ladder of human progress. However, the problem of aversion to learning among adolescents is becoming increasingly prominent. Many scholars have expressed their views on the overview, causes, and solutions to aversion to learning. This paper, by analyzing existing research findings, explores the reasons for adolescent aversion to learning and proposes a series of solutions. These measures cover the family, school, society, and individual levels, aiming to help adolescents overcome their aversion to learning and rekindle their interest in learning.